Building Students' Fluency and Flexibility through The Application of E-Learning Modules Integrated with Education for Sustainable Development (ESD) - Andita Nur Sakinah Lili Budiarti; Amprasto Amprasto; Suparman Suparman (JURNAL BIOEDUKASI, 2025)
This study aims to improve students' creative thinking skills, particularly in the aspects of fluency and flexibility, through the implementation of learning using an e-module enriched with Education for Sustainable Development (ESD) content. The research subjects consisted of 60 ninth-grade students from a junior high school in Rejang Lebong Regency. This study used a quasi-experimental method with a pretest-posttest design. The instrument used was an essay test that had been tested for validity and reliability. The results showed a significant improvement in students' creative thinking skills after implementing the ESD-enriched e-module. The increase in the fluency aspect was reflected in students' ability to generate multiple ideas from a single problem, while the flexibility aspect was evident in students' ability to view problems from various perspectives and produce diverse solutions. The conclusion of this study is that the implementation of ESD-enriched e-modules is effective in enhancing students' creative thinking skills, especially in the aspects of fluency and flexibility.